1978
DOI: 10.1002/eji.1830081109
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of anti‐framework antibodies to the heavy chain variable region (VH) of mouse immunoglobulins

Abstract: The heavy chain variable portion of mouse myeloma protein MOPC-3 15 (a, h z ) was obtained from its Fv fragment (J. Hochman, D. Inbar and D. Givol, Biochemistry 1973. 1 2 : 11 30.) and was used t o immunize rabbits. Rabbit anti-V, antibodies precipitated V,, Fv and the intact protein 315. The V, region specificity of these antibodies was evident from the line of identity in agar gel diffusion between Fv and M315, and from the lack of precipitation with another (11 chain of XRPC-25 or with light (L) chains. Rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

1978
1978
1982
1982

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 15 publications
3
34
0
Order By: Relevance
“…This was because of binding to the heavy (H) chain fragments as judged by direct binding to purified MOPC-315 H-chains and lack of reactivity to constant (C) and to light (L) chains. It should be noted, however, that the reagent does not precisely correspond to that reported by Ben-Neriah et al (13) since only a restricted number of myeloma proteins were bound by this antibody, in contrast to the considerably wider reactivity of the reagent described by Ben-Neriah et al (13).…”
Section: Binding Of (35s)-labeled Proteins To Erythrocytes or Erythromentioning
confidence: 62%
See 2 more Smart Citations
“…This was because of binding to the heavy (H) chain fragments as judged by direct binding to purified MOPC-315 H-chains and lack of reactivity to constant (C) and to light (L) chains. It should be noted, however, that the reagent does not precisely correspond to that reported by Ben-Neriah et al (13) since only a restricted number of myeloma proteins were bound by this antibody, in contrast to the considerably wider reactivity of the reagent described by Ben-Neriah et al (13).…”
Section: Binding Of (35s)-labeled Proteins To Erythrocytes or Erythromentioning
confidence: 62%
“…Antisera with specificity for framework regions of VH chains of Ig were prepared in rabbits after immunization with the myeloma protein MOPC-315, as described previously (13). The MOPC-315 affinity-purified Ig fraction of this antiserum reacted with myeloma proteins MOPC-315, MOPC-460, and, to a lesser extent, T15 and S107.…”
Section: Binding Of (35s)-labeled Proteins To Erythrocytes or Erythromentioning
confidence: 99%
See 1 more Smart Citation
“…Anti-Vn-, anti-variable region of the h light chain (Va), and antivariable region of the x light chain (V,) specific affinity-purified antibodies were prepared by immunizing rabbits with the appropriate myeloma protein fragments, as previously described (13)(14)(15). Previous experiments have suggested that anti-Vn-Ma15 have a selectively lower affinity to AKR VH than to the VH region of C57BL/6 or other mouse strains.…”
Section: Designation Of the Hybridoma Clonesmentioning
confidence: 99%
“…Anti-Vn.315 recognizes allotypelike Igh-l-linked determinants in VH and reacts weakly or fails to react with AKR heavy chains or AKR T cell receptors (10,13,16,19; see also Materials and Methods). This characteristic of anti-Vn was used to investigate the presence of BW-5147 (AKR)-type VH products in the helper factors secreted by clone T77-146-C3.…”
Section: Antigen Specificity and Titer Of The Helper Factorsmentioning
confidence: 99%